Medicaid Patient Experiences with Nurse Practitioners and Other Providers: A Big Data Analysis - DeAnna Jan Emory PhD, RN, CNE; Thomas A. Kippenbrock EdD, RN (Journal of Patient Experience)
There is a current and ongoing shortage of primary care providers that is projected to increase through 2034. Over the last decade, this shortage has resulted in increased reliance on nurse practitioners and physician assistants to fill the gap. The purpose of this study was to investigate Medicaid recipients’ experiences with their respective primary care providers using responses from the Consumer Assessment of Healthcare Providers and Systems database with a focus on nurse practitioners compared to other provider types identified. Responses from 68,761 Medicaid recipients were analyzed. The results showed that Medicaid recipients’ scores for nurse practitioners were comparable to their peer primary care provider types. Areas for improvement were noted. Primary care services provided by nurse practitioners can contribute to the quality goals set by national healthcare organizations for quality and cost-effectiveness of care. This study expands the knowledge about nurse practitioners and other providers in the primary care role.